Wadah Berbagi Pengetahuan Sebagai Variabel Pembantu Dalam Menentukan Strategi Bisnis Konsinyasi Pancake Durian Medan - Syarifah, Laila; W. Sumarlin, Antonius; Purwoko, Bambang (SEKOLAH PASCASARJANA PRESS, 2017)
Basically, the area broadly marketing availability can encourage business environment. One of business strategies shall be guaranteed through consignment. Consignment draw attention many businesses, because of sales value rapid. Despite the highly competitiveness in nature of the business itself, many previous studies have attempted to come up with strategic schemes on how the start up business can kick in and survive overtime. The object of this research is individuals who love Durian Pancake Medan (DPM) and run in consignment business of DPM. DPM was chosen because of highly consumption in Medan, yet it may not apply to the area of Jakarta, Depok and Bekasi where such product at least available and there is also negative perception about durian and its dairy products. Consigment business on pancake durian Medan remains a challenge, particularly in the micro scaled businesses. This research focuses on how businessmen who have capital and the ability to produce DPM, but still have challenge with location of the placement of marketing products with consignment system. There were 95 represented respondents in three areas who were purposively sampled, using questionnaires and processed with PLS analysis. The results of this research prove that the knowledge sharing platform has a role in increasing consumer commitment. There are two criteria for channeling the right place for the formation of strategy consignment business of DPM.